Catalyst‐Free Enantiospecific Olefination with In Situ Generated Organocerium Species. Issue 4 (17th December 2018) - Music, Arif; Hoarau, Clément; Hilgert, Nicolas; Zischka, Florian; Didier, Dorian
Abstract: Described is the in situ formation of triorganocerium reagents and their application in catalyst‐free Zweifel olefinations. These unique cerium species were generated through novel exchange reactions of organohalides with n ‐Bu3 Ce reagents. The adequate electronegativity of cerium allowed for compensating the disadvantages of both usually functional‐group‐sensitive organolithium species and less reactive organomagnesium reagents. Exchange reactions were performed on aryl and alkenyl bromides, enabling enantiospecific transformations of chiral boron pinacol esters. Finally, these new organocerium species were engaged in selective 1, 2‐additions onto enolisable and sterically hindered ketones. Abstract : A cerium way to tolerance : Unprecedented halogen–cerium exchange reactions have unlocked a path to new organometallic species with high functional group tolerance. This versatile process was efficiently applied to enantiospecific catalyst‐free Zweifel olefinations.